EULALIA BERNARD, IN MEMORIAM - Barahona Riera , Macarena (2023)
Within the framework of a social action project of the University of Costa Rica that arose at the beginning of the 2010s, and in collaboration with Radio Universidad, Macarena Barahona and Mónica Perea hosted a radio program called Verso y acorde en voz alta, a space for the reading of poetry in the voice of their own authors, with the aim of rescuing the voices of poets, mainly national and Latin American, although programs with authors from other parts of the world were also carried out. The publication of the collection of poems Tatuaje by Eulalia Bernard Little, motivated the visit of Macarena Barahona to the house of the poetess to record the reading of some of her most recent poems on June 2, 2011, in her house in San Pedro de Montes de Oca. The recording was made by the producer of Radio Universidad, Leo León. Eulalia's poetry is a disruptive poetry with respect to Costa Rican literature of the 70s and 80s. She was a protesting voice, a powerful voice, a woman from migrant families from Jamaica; she made her poetry a flag against racism, against segregation, against patriarchy.